Changes in the technical readiness of volleyball players 10-11 years under the influence of visual perception of movement parameters - Ievgeniia Strelnykova; Yuri Gorchanyuk; Olena Nesen (Kharkiv State Academy of Physical Culture, 2018)
Purpose: increase in the level of technical preparedness of volleyball players at the stage of initial training under the influence of visual perception of the parameters of movements. Material & Methods: 36 female athletes from the initial training group aged 10-11 years old participated in the study in Kharkov. In the course of the study, the following methods were used: analysis of scientific and methodological literature; pedagogical testing pedagogical experiment, methods of mathematical statistics. The pedagogical experiment lasted 8 weeks and was built with the participation of two groups: a control (18 players), the training process of which corresponded to the contents of the Youth Sports School's volleyball program, and an experimental (18 players), the content of the training was supplemented by a program using the technique of technical training, on the basis of visual perception by athletes of the specifics of performing technical techniques. The pedagogical experiment lasted 3 months, after which the changes in the level of technical preparedness of volleyball players of both groups. Results: after the pedagogical experiment, there were established significant improvements in the performance of two test exercises at the athletes of the experimental group. Changes in the results of the volleyball players in the control group were unreliable. Conclusions: our proposed technique of technical training, which is based on the visual perception of athletes of biomechanical peculiarities of performing technical techniques, is effective and can be used by trainers of initial training groups.